FRI0417 Long term influence of nsaids on radiographic progression in patients with ankylosing spondylitis. (23rd January 2014) - Schiotis, R.; Font, P.; Escudero, A.; Buzoianu, A.; Zarco, P.; Almodovar, R.; Gratacos, J.; Mulero, J.; Juanola, X.; Montilla, C.; Moreno, M.; Ariza Ariza, R.; et al.
Abstract : Background: The inhibitory effect of the treatment on styructural damage in AS is not completely understood and it is sill a matter under debate. Recent data indicated that NSAIDs could retard radiographic progression in certain subgroups of patients [1 ], [2 ] Objectives: To investigate the long term influence of NSAIDs on the rate of radiographic progression administrated as continuous vs.on-demand therapy. Methods: Patients included in REGISPONSER with the diagnosis of AS were selected and ought to be administrated only NSAIDs for a period of 3 years. Patients were divided in 2 groups according to NSAIDs intake (continuously vs on-demand). BASRI-spine was applied at baseline and after 3 years. Patients who had the maximum BASRI value of 12 at baseline were excluded form the study. X 2 test, student T test and ANCOVA were applied to compare differences between groups. A logistic regression was performed to analyze the influence of NSAIDs treatment and other factors on the rate of radiographic progression. Results: One hundred eighteen patients were included. No significant differences were found in the two treatment groups at baseline, with exception of disease activity(table 1 ). Significant radiographic progression was identified in the 2 treatment groups after 3 years follow up( p<0.001). The mean BASRI change was 0.66 ± 1.04 in on-demand treatment group vs.0.64 ± 1.22 in continuous treatment group (p-NS after adjustment for symptoms duration). Although in the logistic regression the type of NSAID treatment was not identified as independent predictive factor of increased radiographic damage as were male sex (p= 0.025) and baseline damage (p<0.001), a significant interaction was found between NSAIDs treatment and time-average (ta) CRP (>6 vs. ≤6 mg/L) (OR: 0.04, CI95 %( 0.003-0.524) Conclusions: NSAIDs treatment could not stop radiographic damage in AS. Patients with high CRP level who received NSAIDs on–demand showed the highest progression risk. References: Poddubnyy D, Rudwaleit M, Haibel H, Listing J, Märker-Hermann E, Zeidler H, et al. Effect of non-steroidal anti-inflammatory drugs on radiographic spinal progression in patients with axial spondyloarthritis: results from the German Spondyloarthritis Inception Cohort. Ann Rheum Dis. 2012, 71:1616-22. Kroon F, Landewé R, Dougados M, van der Heijde D. Continuous NSAID use reverts the effects of inflammation on radiographic progression in patients with ankylosing spondylitis. Ann Rheum Dis. 2012;71:1623-9. Disclosure of Interest: None Declared